Lymph node ratio influence on risk of head and neck cancer locoregional recurrence after initial surgical resection: Implications for adjuvant therapy. Issue 6 (30th April 2014) - Prabhu, Roshan S.; Hanasoge, Sheela; Magliocca, Kelly R.; Hall, William A.; Chen, Susie A.; Higgins, Kristin A.; Saba, Nabil F.; El‐Deiry, Mark; Grist, William; Wadsworth, J. Trad; Chen, Amy Y.; Beitler, Jonathan J.
Abstract Background The purpose of this study was to determine if lymph node ratio is associated with locoregional recurrence for patients with oral cavity or laryngeal cancer treated with initial surgical management. Methods The study included 350 patients with oral cavity (73%) or laryngeal cancer (27%) who underwent initial surgery. All analyses were multivariable, adjusting for primary site, pathologic prognostic factors, and adjuvant therapy. Results Lymph node ratio was significantly associated with locoregional recurrence, in which each 1% increase in lymph node ratio had an adjusted hazard ratio (HR) for locoregional recurrence of 1.02 (95% confidence interval [CI], 1.002–1.042; p = .05). Lymph node ratio was also associated with OS, in which each 1% increase in lymph node ratio had an adjusted HR for death of 1.028 (95% CI, 1.012–1.045; p = .001). Conclusion Adjusting for pathologic factors and adjuvant therapy, lymph node ratio was found to be an independent prognostic factor for locoregional recurrence and overall survival (OS). Patients with lymph node ratio ≥20% are at high risk of locoregional recurrence and death, and may be considered for adjuvant chemoradiation. © 2014 Wiley Periodicals, Inc. Head Neck 37: 777–782, 2015